Pemetaan Daerah Banjir Rob Akibat Kenaikan Muka Air Laut di Wilayah Kecamatan Sasak Ranah Pasisie Kabupaten Pasaman Barat - Adawiyah, Nafisah Robbiyatul; Triyatno, Triyatno (Lembaga Yasin AlSys, 2024)
Tidal flooding often occurs in coastal areas and this is sometimes very difficult to predict because it can occur suddenly this happens because sea water is higher than the land surface. This research aims at 1) vulnerability to tidal flooding due to sea level rise,, 2) disaster mitigation of community preparedness. This type of research is quantitative. Data were analyzed using the overlay method and mitigation using the PLS (Partial Least Square) approach, and by taking random sampling of the population. This research results in 1) tides have a formzahl value of 0.31 with a mixed type leaning to double daily occurring twice the tide and twice the ebb with almost the same height, in tidal affected areas have 2 classes, namely vulnerable and not vulnerable areas that are quite vulnerable have an area of 1009 Ha. The distribution of areas classified as quite vulnerable is in areas close to the coast. Areas that are not vulnerable have an area of 11,173 with areas that are not close to the coast. 2) on policies, emergency response plans, disaster warning systems, resource mobility is able to explain the preparedness variable by 60.9%. Based on the results of these calculations it can be concluded that this research model is included in the moderate or moderate category. Because if > 0.50 indicates a moderate model.